Salt accumulation and distribution in a greenhouse soil as affected by salinity of irrigation water and leaching management - Blanco,Flávio F. (2002)
The effects of irrigation water salinity, leaching fraction and its frequency of application on soil salinization were studied. Three water salinities (S1=1.54, S2=3.10 and S3=5.20 dS m-1) and two irrigation water depths associated with their application frequencies (W1=1.00 ETc; W2F1=1.25 ETc in all irrigations and W2F2=1.25 ETc when the irrigation water depth of W1 reached 100 mm where ETc is the crop evapotranspiration), were applied during the growing period of a grafted-cucumber crop in a greenhouse. The experimental design consisted of randomized blocks of 3 x 3 factorial scheme with 3 replications. Soil salinity at 0.1, 0.3 and 0.5 m depths increased linearly with salinity levels of water and the leaching fraction did not have any effect regardless of its management. Salt concentration was higher near the soil surface and between the adjacent drippers.